(untitled) (Studia Prawnicze / The Legal Studies, 2012)
Polish Code of Civil Procedure („CCP”) has traditionally, following the Austrian tradition of “social model of litigation”, placed the responsibility for the swift resolution of a civil dispute on a judge. Thus, judicial case management has been the second main doctrine, aside from the doctrine of concentrated proceeding, that has been utilized in ensuring that justice in done without unreasonable delay. Simultaneously, both of these systems adopted the rule, introduce by French Code of civil procedure of 1806, that parties are allowed to make allegations and introduce evidence until the very end of the main hearing (trial). Under Polish law this rule was eliminated only in special proceedings for commercial matters, which will be abolished effective May 3, 2012, where the principle of preclusion (Präklusivprinzip) was introduced over 10 years ago. This rule, and its essential component, the principle of eventuality or contingent cumulation (Eventual maxime), required parties to provide full account of allegations and evidence in their respective pleadings (complain and answer), including those that might only potentially come into play. Failure to comply with this requirement rendered allegation or evidence late, and thus the court was obliged to ignore them, save two limited circumstances. The practical effect of this rule was problematic. Some time ago is was noted that the regular proceedings lacked a general provision that would underline the parties’ responsibility for the effective conduct of litigation and special rules that would stimulate them to make allegations and submit evidence as early as possible. One of the primary purposes of the recent amendments to the CCP was to address these procedural defects. Accordingly, on May 3, 2012 a new art. 6 § 2 CCP comes into force. It stipulates that the parties are obliged to make all statements of fact and present evidence without delay, so that the proceeding can be concluded efficiently and swiftly. This solution is based on German and Austrian procedural ideas (Prozessförderungspflicht). This procedural burden is sanctioned by new art. 207 § 6 CCP. Under this provision court is obliged to ignore (exclude) late allegations and evidence, unless a party shows that their omission from the complaint, answer to complain or further supplementary pleading can be excused due to lack of negligence or the acceptance of late allegations and evidence does not delay the resolution of the case or other extraordinary circumstances justifying their inclusion. Similar rule has been introduced at the main hearing where, however, it is up to the court to decide whether an allegation has been made or evidence presented in a belated manner (art. 217 § 2 CCP). I this article I am focusing on “lack of delay” as an exception to the court’s obligation to exclude late allegations and evidence. I am discussing the scope of the burden to support the orderly, efficient and swift conduct of the litigation by making proper allegations and identifying respective evidence in the pleading. Next, I look into German law to gain a comparative perspective on the new law. Subsequently, I am discussing how a party should make and how, on the other hand, the court should asses a claim of lack of delay in a broader procedural context of judicial case management.